DCF and Real Options in Company Valuation: a Case Study at a Small High-growth Firm--TMIC - YANG, TAO (2006)
This dissertation discusses the application of real options theory in estimate of intrinsic value of a small high-growth software company which has great uncertainties on the strategic project. Traditionally, discounted cash flow (DCF) models are most commonly used in capital budgeting. However, it is argued that DCF models fail to account for the managers' ability to alter the course of investment over time responding to the new information, thus they are likely to underestimate strategic investment. By introducing real option theory and option pricing models, it becomes intuitive to use real options analysis to calculate a project's embedded option value.